Numerical Analysis of Flow Stability in a Natural Circulation Loop - Muhammad Aulia Rahman; Prastowo Murti; Muhammad Arifin Ilham (Jurnal Inotera, 2024)
Flow modeling of a natural circulation loop is of high importance in ensuring the stability of the system. As a system relying on buoyancy force, several parameters play a crucial role in determining stability. In this study, a one-dimensional numerical model is employed to predict the mass flow rate and stability due to the variation of heated riser and cooled faller locations. The result shows that the highest flow rate of 0.344 kg/s is obtained as the heater is located at the lowest position, while the cooler remains at the top. Furthermore, a stability map is plotted to show the condition for the stability, whereby the result demonstrates that the location with a relatively low mass flow rate exhibits a higher chance of oscillating flow.